1991
DOI: 10.1093/jn/121.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Low Zinc Intake Affects Maintenance of Pregnancy in Guinea Pigs

Abstract: Zinc deficiency during pregnancy has severe effects in animals. To what extent the effects in animals apply to human pregnancy is not known. Because the pregnant guinea pig shares characteristics with pregnant women that make it a useful model, three experiments were done with guinea pigs in which Zn intake was reduced beginning on the 30th d of gestation. Reduced Zn intake in two of the three experiments resulted in abortion or premature delivery. Zinc-supplemented animals with feed intake restricted to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…It is well known that maternal Fe deficiency anaemia increases preterm delivery and low birth weight (Scholl and Hediger, 1994), and severe Zn (Masters et al, 1983;Apgar and Everett, 1991) or Cu (Hall and Howell, 1969) (fig 3).…”
mentioning
confidence: 99%
“…It is well known that maternal Fe deficiency anaemia increases preterm delivery and low birth weight (Scholl and Hediger, 1994), and severe Zn (Masters et al, 1983;Apgar and Everett, 1991) or Cu (Hall and Howell, 1969) (fig 3).…”
mentioning
confidence: 99%
“…Apgar et al , showed that zinc intake affects the maintenance of guinea pig pregnancy. [46] Also, Graham et al , in 2009 demonstrated that serum zinc and copper concentrations had a positive correlation with spontaneous abortion in cows. [47] In this study, patients with RSA who responded to LIT due to their positive cross-match had higher serum zinc levels than those with negative cross-match test.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of a Zn-deficient diet in mice during pregnancy can result in severe embryonic and fetal pathologies including prenatal death and a high incidence of central nervous system, soft tissue, skeletal defects, and postnatal behavioral abnormalities (NRC, 1995). Apgar and Everett (1991) reported abortion and premature delivery in Zn-deficient guinea pigs. Hamsters raised on a Zn-deficient diet showed weight loss, cessation of growth, and disruption of estrus cycle.…”
Section: Other Animal Speciesmentioning
confidence: 99%